Auditoría Tributaria y su determinación en el riesgo fiscal de RIO BG Distribuciones de la Ciudad de Riobamba, período 2017 - Aguayo Tene, Franklin Eduardo (2019)
The present research project appointed "TAX AUDIT AND ITS DETERMINATION IN THE FISCAL RISK FOR RIO BG DISTRIBUTIONS OF THE CITY OF RIOBAMBA, PERIOD 2017" refers to the referential framework which explains: the Problem Statement, the formulation of the problem, the objectives : general and specific and the justification of the research, then reference is made to the theoretical framework: where the generalities of the company were addressed, it also includes definitions that helped us to for a better understand the research, in addition to the methodological framework: where It made known the methodology, the type of research, the techniques and instruments and the population and shows it was used for the purposes of this research, then it deals with the result and discussion of the research: for which reference is made to the audit process carried out within the research such as: planning, execution and presentation of the results; and also the most relevant findings of the research that should be exposed with corrective purposes and finally the conclusions and recommendations were presented where the researcher took as a main base the information that the company has as support of their economic activities during 2017 year of the exam.